Association between sarcopenia and outcomes of surgically treated oral squamous cell carcinoma: a systematic review and meta‐analysis - Luo, Kai; Chen, Kaiming; Li, Yu (Frontiers in Oncology, 2024)
BackgroundSarcopenia is a significant predictor of perioperative adverse outcomes for a variety of malignancies and has significant negative effects on surgical and oncology outcomes. The development of sarcopenia is mainly attributed to aging, inactivity, poor nutrition, and decreased testosterone levels, which suggest a poor prognosis after surgery. Therefore, the primary objective of this systematic review and meta-analysis was to determine the effect of sarcopenia on postoperative survival in patients with oral squamous cell carcinoma.MethodsWe systematically searched databases including PubMed, Embase, Cochrane Library, Medline and Web of Science from inception to 12 July 2023, to determine the prognostic value of sarcopenia in oral squamous cell carcinoma. The primary outcome was three-year survival, and secondary outcomes were one-year survival, five-year survival, infection and pneumonia within 30 days postoperatively. Original studies comparing postoperative outcomes in patients with sarcopenia and non-sarcopenia for oral squamous cell carcinoma curative therapy were met the eligibility criteria. We used Endnote X9 for the screening process and used RevMan 5.4.1 for our meta-analysis, all results in this study were performed using a random-effects model. QUIPS (Quality in Prognosis Studies) tools and GRADE (Grading of Recommendations, Assessment, Development and Evaluations) were used for risk of bias and quality of evidence assessment.ResultTen original studies with 50611 patients met the inclusion criteria. Meta-analysis showed that patients with sarcopenia reduced three-year OS after surgery (OR = 0.73, 95% CI = 0.66-0.81, P < 0.00001). The one-year OS (OR = 0.71, 95% CI = 0.67-0.75, P < 0.00001) and five-year OS (OR = 0.60, 95% CI = 0.45-0.79, P = 0.0003) decreased significantly. Patients with sarcopenia had significantly increased 30-day postoperative mortality and an also increased risk of pneumonia (OR = 1.36, 95% CI = 1.24-1.49, P < 0.00001) and surgical site infection (OR = 2.49, 95% CI = 1.06-5.84, P = 0.04).ConclusionSarcopenia is associated with reduced survival in patients after curative resection. Meanwhile, 30-day mortality, postoperative pneumonia and surgical site infection were significantly higher than those in nonsarcopenic patients. Sarcopenia as an extremely important factor of postoperative adverse outcomes in OSCC patients need special attention.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42023444424.